2019
DOI: 10.1002/chem.201804953
|View full text |Cite
|
Sign up to set email alerts
|

Difluorodiazoethane (CF2HCHN2): A New Reagent for the Introduction of the Difluoromethyl Group

Abstract: Difluorodiazoethane (CF 2 HCHN 2 )i sasmall reactive diazoalkane. Its synthesis has been pursued since the 1970s, although only in the past three years have considerable advances been made. To day,d ifluorodiazoethane is av ersatile reagent applied in [3+ +2]-cycloadditions, esterification, and carbene transfer reactions. Difluorodiazoethane possesses markedlya lteredr eactivity compared to the well-studied trifluorodiazoethane (CF 3 CHN 2 ). In this article, we discuss the differences between the two reagents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 81 publications
0
24
0
Order By: Relevance
“…A recent publication by AbbVie chemists attracted our attention; they described flow reactor‐based cyclopropanation of various styrylboronic esters with diazomethane on up to 2.4 mmol scale [35] . Although we had some concerns about using this dangerous reagent, recent procedures for safe generation and handling of diazoalkane solutions [46–48] prompted us to consider this approach for the cyclopropanation of 5 . It was found that a reaction of 5b with CH 2 N 2 in t BuOMe in the presence of Pd(OAc) 2 (5 mol‐%) proceeded with high efficiency already at 0 °C and gave target cyclopropane derivative 11b in 73 % yield (58.9 g scale) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…A recent publication by AbbVie chemists attracted our attention; they described flow reactor‐based cyclopropanation of various styrylboronic esters with diazomethane on up to 2.4 mmol scale [35] . Although we had some concerns about using this dangerous reagent, recent procedures for safe generation and handling of diazoalkane solutions [46–48] prompted us to consider this approach for the cyclopropanation of 5 . It was found that a reaction of 5b with CH 2 N 2 in t BuOMe in the presence of Pd(OAc) 2 (5 mol‐%) proceeded with high efficiency already at 0 °C and gave target cyclopropane derivative 11b in 73 % yield (58.9 g scale) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Fluoroalkyl diazo compounds have been recognized as a versatile reagent for introducing fluorinated groups over the last decade, and their synthetic potential has attracted continuous interest, particularly in asymmetric synthesis. However, the potential toxicity and explosiveness of fluoroalkylsubstituted diazo compounds limit their safe and scalable applications [20][21][22][23][24]. Fluoroalkyl N-sulfonyl hydrazones have been developed and used as operationally safe diazo surrogates in carbene transfer reactions in this context.…”
Section: Asymmetric Reactions Of Fluoroalkyl N-sulfonyl Hydrazonesmentioning
confidence: 99%
“…Although first described in 1943 [19], the synthetic applicability of trifluorodiazoethane has started emerging only in the past decade. Many exciting new reactivities and fluoroalkyl-substituted diazo compounds have been developed as valuable reagents for the quick introduction of fluorinated side chains [20][21][22][23][24]. However, these reagents' safe and scalable applications have generally been hampered by their potential toxicity, explosive properties, and abnormal reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the use of fluorinated diazoalkanes proved very fruitful and numerous methods were uncovered in recent years to access valuable fluorinated pyrazoles following this strategy. 2,3 Another reactivity of diazoalkanes lies within their basicity that allows deprotonation reactions of carboxylic acids followed by esterification reactions and proved particularly useful for the synthesis of methyl esters with diazomethane or (trimethylsilyl)diazomethane. Upon extrusion of dinitrogen, e.g.…”
Section: Introductionmentioning
confidence: 99%